Staffing Organizations - G. Heneman Herbert; A, Judge Timothy (New York : MC Graw Hill, 2009)
Heneman and Judge’s Staffing Organizations, 6/e, is based on a comprehensive staffing model. Components of the model include staffing models and strategy, staffing support systems (legal compliance, planning, job analysis and rewards), core staffing systems (recruitment, selection, employment), and staffing system and retention management. Up-to-date research and business practices are the hallmarks of this market leading text. In-depth applications (cases and exercises) at the end of chapters provide students with skill-building and practice in key staffing activities and decision-making. A comprehensive running case involving a fictitious retailing organization provides even greater opportunity for in-depth analysis and skill building. Students also have the opportunity to address ethical issues at the end of each chapter.
Keywords: Employees--Recruiting; Employees selection